Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14159535
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Application Decreases the Enrichment and Human Exposure Risk of Cadmium in the Leaf of Jute (Corchorus capsularis L.) Planted in Uncontaminated Purple Soil

Abstract: The effects of soil selenium (Se) application on the enrichment and human exposure risk of heavy metals in the jute (Corchorus capsularis L.) leaf have attracted extensive attention. The jute was planted with or without soil Se addition for 265 days. The jute leaf was harvested seven times during the experiment to determine the content of lead (Pb), cadmium (Cd), and Se. The results showed that the enrichment ability ranked Cd > Se > Pb. Cd in the jute leaf exceeded the average pollutant limit in GB2762-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…In this study, using field experiments combined with indoor simulation, we revealed the migration characteristics of soil effective selenium measured in situ under drip irrigation, and found that drip irrigation significantly affected the distribution of effective selenium in the soil, and its migration characteristics were strongly affected by the amount of water drop and soil type [8]. The results provide an important scientific basis for precision drip irrigation technology in improving the nutritional management of selenin and ensuring fruit quality, and have certain reference value for promoting the wide application of drip irrigation technology in agricultural production [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, using field experiments combined with indoor simulation, we revealed the migration characteristics of soil effective selenium measured in situ under drip irrigation, and found that drip irrigation significantly affected the distribution of effective selenium in the soil, and its migration characteristics were strongly affected by the amount of water drop and soil type [8]. The results provide an important scientific basis for precision drip irrigation technology in improving the nutritional management of selenin and ensuring fruit quality, and have certain reference value for promoting the wide application of drip irrigation technology in agricultural production [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that under the action of drip irrigation, the distribution of selenium in the soil showed obvious hierarchy, and the selenium content in the surface soil was high, which gradually decreased with the increase of depth. This phenomenon indicates that water dripping can block the vertical migration of selenium in the soil [10].…”
Section: Relationship Between Growth Of Pomelo and Effective Selenium...mentioning
confidence: 97%